1991
DOI: 10.1577/1548-8640(1991)053<0017:tojlte>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Juvenile Lake Trout Exposed to Gas Supersaturation

Abstract: Lake trout (Salvelinus namaycush) 2.9–3.9 cm long that were exposed to five gas supersaturation levels ranging from ▵P 9 to ▵P 159 mm Hg above saturation for 30 d grew at the same rates. Survival was also virtually equal in all treatments, ranging from 93% at ▵P 42 to 99% at ▵P 126. After 30 d, signs of gas bubble disease were evident at ▵P 126; 3% of fish had exopthalmia and 12% had bubbles in the nares. At ▵P 159, 20% had bubbles inside the mouth or on the conjunctiva, or rim of the orbit, plus 3% had exopth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Treatments ranged from 8 to 210 mm Hg (SD ¼ 18 mm Hg) and were highly variable, fluctuating two to three times more than the variation experienced with our system. Another experiment, employing a design similar to ours, mixed a supersaturated water source with a saturated one after injecting air into a pressurized vessel, maintaining treatment levels of 4-75 mm Hg (SD ¼ 10 mm Hg; Krise and Smith 1991). This variation was similar to our maximal variation at the highest treatment but roughly twice that observed under similar DPs in our oxygen enrichment and chronic studies.…”
Section: Discussionsupporting
confidence: 75%
“…Treatments ranged from 8 to 210 mm Hg (SD ¼ 18 mm Hg) and were highly variable, fluctuating two to three times more than the variation experienced with our system. Another experiment, employing a design similar to ours, mixed a supersaturated water source with a saturated one after injecting air into a pressurized vessel, maintaining treatment levels of 4-75 mm Hg (SD ¼ 10 mm Hg; Krise and Smith 1991). This variation was similar to our maximal variation at the highest treatment but roughly twice that observed under similar DPs in our oxygen enrichment and chronic studies.…”
Section: Discussionsupporting
confidence: 75%
“…In the only study we are aware of (Counihan et al 1998), white sturgeon embryos were resilient to GBT but the vulnerability of sturgeon larvae varied with the stage of development (Counihan et al 1998). This is consistent with salmonids, whose embryos are resilient to GBT (Alderdice and Jensen 1985), larvae experience some level of GBT, and juvenile and adults are the most sensitive to GBT (Krise and Smith 1991). White sturgeon feed and live near the deep areas of rivers (Hildebrand et al 1999) where depth has been shown to provide protective effects to GBT (Antcliffe et al 2002;Pleizier et al 2020a).…”
Section: Introductionmentioning
confidence: 67%